(untitled) - Dacey, John S. (San Francisco, 1998)
This book combines the wonder and awe of human creativity with the complexity of its study. The authors advance the ?biopsychosocial' perspective as a model of the creative process. . . . This new perspective promises to further our understanding of the ?intricacies of the creative mind.' In the process of studying this book, readers may increase the probability of enhancing their own creativity. --Richard E. Ripple, professor, educational and developmental psychology, Cornell University
Keywords: Creative ability,Creative thinking,Khả năng sáng tạo,Tư duy sáng tạo